Anticancer activities of mushroom polysaccharides on chemically-induced colorectal cancer in rats - Sorial A. Moharib, Nabila Abd El Maksoud, Halla M. Ragab and Mahmoud, M. Shehata (Journal of Applied Pharmaceutical Science, 2014)
Polysaccharides from mushroom Pleurotus sajor-caju (PS1) and Lactuca sativa (PS2) were isolated and purified (22.40 and 26.80g/100g respectively). Cytotoxic activities of PS1 and PS2 were examined In vitro using colon (HCT 116), liver (HEPG2), cervical (HELA) and breast (MCF7) carcinoma cell lines. The present results indicated that these polysaccharides (PS1 and PS2) have more inhibitory effects on HCT-116 than the other carcinoma cell line (HEPG2, HELA and MCF7). Polysaccharides (PS1 and PS2)-treated HCT-116 cells showed a high percentage of cell death, indicating promising anti-tumorigenic properties, and demonstrate their direct effect on colon cancer cell proliferation. Evaluation of the two polysaccharides (PS1and PS2) was carried out through determination of the tumor markers (CEA and C19.9) in cancer rat groups treated with either PS1 or PS2 compared versus carcinogenic control rats. Polysaccharides (PS2) administration caused higher inhibitory effect on chemically-induced colorectal cancer in rats through the histological examination and a marked reduction in the levels of ALP and ALT more than that of PS1 in serum of rats. It can be concluded that polysaccharides (PS1 and PS2) are more effective for inhibition of chemically induced colorectal cancer in rats.
Keywords: Mushroom, Lactuca Sativa, Polysaccharides, Cytotoxicity, DMH, Rat.